Empowering Malaysian dentists to tobacco dependence treatment conduct - Amer Nordin, Amer Siddiq; Abdul Kadir, R.; Yahya, N.A.; Zakaria, H.; Abd Rashid, Rusdi; Habil, H. (Wiley, 2014)
As a signatory to the World Health Organisation 2003 Framework Convention on Tobacco Control, Malaysia has policies in place and funded 300 public Quit clinics. Unfortunately, government dentists are not included to run tobacco dependence treatment. A cross-sectional exploratory survey was carried out to seek Malaysian dentists' opinion on their knowledge, perception and willingness to conduct tobacco dependence treatment. Participation was voluntary from those who attended a specially designed one-day, four-module workshop on tobacco cessation intervention. Data were collected using the Audience-Response-System equipment which tracked immediate responses covering four domains namely: smoking as a public health problem, smoking as an addiction, the role of dentists in the programme and confidence in conducting smoking cessation in the clinic. Sample comprised more female dentists (73.5), mean age 33.6 (SD 8.99) years and with more than 3 years working experience. Findings indicated that the majority agreed Malaysia has a rising problem in the prevalence of smoking (71.6) and predicted that it will affect mostly the young (81.9). Only half of the dentists surveyed (58.9) routinely recorded their patients' smoking habits. The majority (71.6) believed that dentists are effective in helping their patient to stop smoking and 76.3 agreed that dentists should discuss the smoking habit with their patients; however, 60 agreed that doing so is too time consuming. In addition, only 24.7 knew of more ways to treat a smoking habit. The majority felt comfortable giving advice to patients about changing their habits (76.5) or discussing treatment options (60.5): 75 would opt for a combined programme of counselling and use of medication if they have to do, 15 would choose to go on counselling only, while 8 did not want to treat. In conclusion, the findings suggest that dentists have a strong potential to contribute significantly to providing smoking cessation treatment if adequately trained.